Exploration and Practice of Advanced Algebra Curriculum Development in the Context of Emerging Engineering Disciplines: A Case Study of the Data Computing and Applications Program - Wang, Jing (Journal of Educational Research and Policies, 2025)
Under the dual background of the New Engineering Education reform and big data technology development, this study explores innovative approaches for cultivating talents in Data Computing. As an emerging interdisciplinary program integrating mathematics, statistics, and computer science, the Data Computing and Applications major requires students to possess solid mathematical foundations and data processing capabilities. Focusing on the teaching reform of Advanced Algebra - a core course of this major, this research proposes three key initiatives: (1) optimizing teaching content through interdisciplinary integration with Analytical Geometry; (2) innovating teaching methodologies by incorporating case-based instruction, mathematical modeling, and flipped classroom approaches; (3) developing specialized textbooks tailored to New Engineering needs. These reform measures aim to cultivate high-quality applied talents meeting the national digital economy development requirements.